CO2 methanation over γ-Al2O3 nanosheets-stabilized Ni catalysts: Effects of MnOx and MoOx additives on catalytic performance and reaction pathway. (September 2022) - Chen, Jiahui; Shen, Xuqiang; Wang, Qiaojuan; Wang, Jianyue; Yang, Dan; Bold, Tungalagtamir; Dai, Yihu; Tang, Yongming; Yang, Yanhui
Abstract: With 5 nm Ni nanoparticles anchored by the nanosheet-shaped γ -Al2 O3 supports, a 10 wt% Ni/Al2 O3 catalyst displayed ca. 45% conversion and >98% CH4 selectivity in CO2 methanation reaction at 300 °C for 450 h. Benefited from stable interfaces between Ni sites and highly dispersed MnOx promoters on Al2 O3, a modified Ni-Mn/Al2 O3 catalyst exhibited 93–88% conversions, >99.9% selectivity and great stability in 1100 h reaction. As a contrast, a Mo-modified Ni-Mo/Al2 O3 catalyst showed severe deactivation with declined conversions from >80 to 50% within initial 20 h. The high-dispersion MoOx species in the fresh catalyst occurred aggregation and reduction during the reaction, reconstructing the Ni-support interfaces. As clarified by in-situ DRIFT spectra, the COads -mediated hydrogenation reaction pathway was followed on these Ni catalysts via sequential steps, CO2 → bicarbonates → bidentate carbonates → bidentate formates → COads → CH4 . Ni-Mn/Al2 O3 catalyst exhibited significantly high and well-matched reaction rates in overall steps, whereas Ni/Al2 O3 catalyst showed low activities in key steps of formate decomposition and COads methanation. Ni-Mo/Al2 O3 catalyst displayed superior ability for CO2 dissociation into bicarbonates, and nonetheless, it could not steadily achieve the formation and hydrogenation of COads species, allowing the inactive surface species to be accumulated and to induce the catalyst structural change for deactivation. Graphical Abstract: ga1 Highlights: γ -Al2 O3 nanosheet can stabilize active Ni sites for steadily catalyze CO2 methanation. MoOx additive promotes initial activity but causes deactivation due to aggregation and reduction. MnOx promoter tunes Ni-support interaction to enhance activity and stability in 1100 h reaction. Ni-Mn/Al2 O3 catalyst follows COads -mediated hydrogenation reaction route in CO2 methanation. Ni-Mn/Al2 O3 catalyst exhibits high and well–matched reaction rates for sequential key steps.